2006
DOI: 10.2478/s11756-006-0171-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation of nitrates in runoff from mountain and rural areas

Abstract: The paper presents results of temporal and spatial variation of nitrates in streamwater in the small mountain catchment of the Jalovecký creek, the Western Tatra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…On the other hand, the highest concentrations occur mostly in the initial snowmelt stage. Then the nitrogen compounds are leached out from the snow cover and soil (Johannessen and Henriksen 1978;Holko et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the highest concentrations occur mostly in the initial snowmelt stage. Then the nitrogen compounds are leached out from the snow cover and soil (Johannessen and Henriksen 1978;Holko et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Pekárová & Miklánek (2005) and Pekárová et al (1999) showed the development of nitrate concentrations in the Mošteník basin (Slovakia), and the nitrogen balance and modelling of its agricultural subbasin, Rybárik, and forested subbasin, Lesný, during the period 1988-1992. The water quality in Slovak experimental microbasins (Mošteník, Ondava and Jalovecky brook), nitrate concentrations, their trends and losses between 1986 and 2005 were evaluated by Pekárová & Pekár (1996), Halmová (1996), Holko et al (2004Holko et al ( , 2006, and Lichner et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Jalovecky creek basin (Holko et al 2003;Holko et al 2006) is one of the experimental basins of the Institute of Hydrology SAS. Its area covers 22.2 km 2 and the elevations range from 800 to 2178 m a.s.l.…”
Section: Case Study Resultsmentioning
confidence: 99%